(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The archaeological site of Castillo de Doña Blanca, in the Bay of Cadiz, has provided in the course of official excavations a numerous group of brief inscriptions in Phoenician scripture and language. Some of the documents are among the oldest found in the Peninsula, testimony of the use of the scripture by the western Phoenicians. Therefore, they are a fundamental part in the study of the phoenician influence in the origins and development of the scripture among the peoples of the ancient Iberian Peninsula. We present here an exhaustive synthesis of the finds (indicating location, chronology, type of materials, objects, as well as the contents and essential characteristics of the pieces), in order to appreciate its importance and historic value, as an advance of the next publication of the whole group.